Effects Of Leisure Education Programme On Leisure Benefits And Motivation Among Rural Iban Adolescents In Sibu, Sarawak - Saimon, R.; Lee, C.L; Chana, H.N (2017)
Introduction: Leisure education is becoming an important concept in the Western world, but less established and practiced in Malaysia. Evidence has shown the positive effects of leisure education programme to reduce adolescent’s engagement in risky behaviours, such as substance use, sexual behaviour, obesity, and internet addiction, which are detrimental to adolescent’s health and well-being. This study was aimed to examine the effects of leisure education programme on leisure benefits and motivation aspects among rural Iban adolescents in Sibu, Sarawak. Methods: The study employed a pre-post evaluation design. Convenience sampling was used to select the participants.Thirty four Iban adolescents from two longhouses had completed 9-hour leisure education programme for three weeks. Respondents were surveyed before and immediately after the intervention to observe changes in knowledge of leisure benefits and free time motivation scales. Data were analyzed with the use of Wilcoxon signed ranks tests. Significance level was set at p<0.05. Results: The leisure education intervention showed improvement in respondent’s knowledge on benefits of leisure time, but no significant changes was detected in all five motivation types (intrinsic, amotivation, extrinsic, introjected and identified). Conclusion: The leisure education intervention conducted had effectively improved the knowledge of the respondents on leisure benefits. Therefore, leisure education service can be considered to promote a balanced and healthy leisure lifestyle among adolescents.